Alat Tanam Jagung dengan Kontrol Jarak Tanam dan Kualitas Biji Berdasarkan Ukuran - Roza Susanti; Nadia Alfitri; Anton Hidayat; Rieke Syochrani Zaef; Yul Antonisfia (Elektron : Jurnal Ilmiah, 2022)
A corn planting tool has been made by controlling spacing and seed quality based on size. The aim of this research is to make a prototype corn planting tool with plant spacing and seed quality control based on microcontroller controlled size. The research method starts from making a prototype, and measuring system performance. The results of measuring the performance of the tool are indicated by an error in the reading of the HC-SR04 ultrasonic sensor at a point of 2 cm with an error value of 10% which is close to the actual measurement value, while for reading the distance on the ultrasonic sensor at a point > 2 cm it can be said to be constant to the actual distance. The test results of the BTS7960 motor driver work according to the system work description and are able to control the pulse width modulation (PWM) and the direction of rotation of the DC motor properly. The 28BYJ-48 stepper motor can operate the seed rationing system properly and accurately to rotate the motor at an angle of 90o takes 30 seconds. Overall the tool can function properly. Suggestions for further research, can be added monitoring of corn planting results based on the Internet of Things (IoT).